A METHOD OF VERIFYING THE ROBOT'S TRAJECTORY FOR GOALS WITH A SHARED WORKSPACE - Jakub ANCZARSKI; Adrian BOCHEN; MArcin GŁĄB; Mikolaj JACHOWICZ; Jacek CABAN; Radosław CECHOWICZ (Applied Computer Science)
The latest market research (Fanuc Polska 2019) shows that the robotization of the Polish industry is accelerating. More and more companies are investing in robotic production lines, which enable greater efficiency of implemented processes and reduce labour costs. The article presents the possibilities of using virtual reality (VR) for behavioural analysis in open robotic systems with a shared workspace. The aim of the article is to develop a method of verification of programmed movements of an industrial robot in terms of safety and efficiency in systems with a shared workspace. The method of the robot program verification on the digital model of the working cell made in VR will be checked. The obtained research results indicate a great potential of this method in industrial applications as well as for educational purposes.